Sikap Masyarakat Jalan Sentosa Lama GG Perwira Kel. SEI Kerahulu Kecamatan Medan Perjuangan Medan Terhadap Pentingnya Pendidikan Islam - Afrahul Fadhila Daulai; Khairul Azmi; Anggi Rahmanida Nasution; Aisyah Rizqa Siregar; Yusriani Yusriani; Ardina Khoirunnisa Hasibuan (Universitas Muhammadiyah Enrekang, 2022)
This study discusses the attitude of the community towards the importance of Islamic education on Jalan Sentosa Lama, the alley of the Medan Struggle District Officers. This study aims to determine the public’s attitude towards the importance of Islamic education on Jalan Sentosa Lama alley of the district officer. Battlefield. To identify the contribution of society in the implementation of Islamic education for the younger generation. The type of research conducted is descriptive qualitative. The source of the research data is purely the result of the field by interviewing a person from the community. The results of the study showed that there was still a lack of knowledge about Islamic values ​​in the community, it was proven that the number of worshipers was small even though the mosque in the neighborhood was very close. The opportunity for implementing Islamic religious education for the younger generation is very small because at this time they can argue and also they spend more time with useless things, one of which is by playing gadgets